2015
DOI: 10.1177/1541931215591309
|View full text |Cite
|
Sign up to set email alerts
|

Product warnings and the involuntary capture of attention

Abstract: In both published papers and in guidelines of regulatory agencies and voluntary standards, examples can be found where the assumption is made that what will capture attention is that which is salient or conspicuous, and that these qualities are both necessary and sufficient to capture attention. A review of the published, peer-reviewed literature on attention capture, however, invites the conclusion that there are very few features of an object that will draw attention to themselves without or against the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The process by which a person, such as a driver, allocates their cognitive capacity to focus on environmental features is known as attention , and the analogous process by which the person directs their ocular gaze to certain features within their field of view is referred to as visual search . Decades of research have demonstrated human visual search to be dependent on context, including task demands and situational factors (Rauschenberger, 2003; Rauschenberger et al, 2015). For drivers, gaze and attention allocation are heavily influenced by the salience of the environmental information’s source, the driver’s perceived likelihood that the source will provide useful and relevant information, the perceived costs in the hypothetical event relevant information is missed, and the perceived effort involved in attending to the source (Horrey et al, 2006; Land, 2006).…”
Section: Visual Perceptionmentioning
confidence: 99%
“…The process by which a person, such as a driver, allocates their cognitive capacity to focus on environmental features is known as attention , and the analogous process by which the person directs their ocular gaze to certain features within their field of view is referred to as visual search . Decades of research have demonstrated human visual search to be dependent on context, including task demands and situational factors (Rauschenberger, 2003; Rauschenberger et al, 2015). For drivers, gaze and attention allocation are heavily influenced by the salience of the environmental information’s source, the driver’s perceived likelihood that the source will provide useful and relevant information, the perceived costs in the hypothetical event relevant information is missed, and the perceived effort involved in attending to the source (Horrey et al, 2006; Land, 2006).…”
Section: Visual Perceptionmentioning
confidence: 99%